Penegakan Hukum Undang Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan Terhadap Pengendara Anak Usia Sekolah di Wilayah Kota Malang (Studi Kasus Pada Satuan Lalu Lintas POLRESTA Malang) - Firman Widyaputra* (Universitas Airlangga, 2017)
The condition of transportation as one of the pillars of the movement of people from one place to another safely, comfortably, quickly, cheaply in accordance with the environment, with the increasing growth rate of motor vehicles (four-wheeled and two-wheeled) is not balanced with the physical road, so that more dense road transportation, especially in the city, with the socio-economic development of the community will affect parents who provide concessions to their children who have not met the age of driving a motor vehicle, especially two wheels. Thus it will affect the road traffic and will result in the occurrence of violations and accidents. The approach to be used is a normative juridical approach or statutory approach, namely research that examines laws relating to road traffic and transportation in accordance with Law No. 22/2009 concerning Traffic and Road Transportation. In addition to this approach, the authors also carried out a sociological approach which can empirically be known symptoms of changes in community behavior towards social development in society related to road users in Malang. Existence in legislation relating to road users in traffic can be obeyed and minimize the occurrence of violations, crime, safety and comfort, and accidents. Thus the violation of the law will be reduced and order will be well realized.